Combined RhoA morpholino and ChABC treatment protects identified lamprey neurons from retrograde apoptosis after spinal cord injury - Hu, Jianli; Zhang, Guixin; Rodemer, William; Jin, Li-Qing; Selzer, Michael E. (Frontiers in Cellular Neuroscience, 2023)
Previously, we reported that RhoA knockdown by morpholino antisense oligonucleotides (MOs), and enzymatic digestion of chondroitin sulfate proteoglycans (CSPGs) at the site of injury with chondroitinase ABC (ChABC), each can reduce retrograde neuronal apoptosis after spinal cord transection in the lamprey. To elucidate the mechanisms in neuronal survival and axon regeneration, we have investigated whether these two effects are additive in vivo.We used lampreys as a spinal cord injury model. MOs were used to knockdown RhoA and Chondroitinase ABC (ChABC) was used to digest CSPGs in vivo. Retrograde labelling, fluorochrome-labelled inhibitor of caspase activity (FLICA), immunohistochemistry, and western blots were performed to assess axonal regeneration, neuronal apoptotic signaling and Akt activation. Four treatment combinations were evaluated at 2-, 4-and 10-weeks post-transection: 1) Control MO plus enzyme buffer (Ctrl); 2) control MO plus ChABC; 3) RhoA MO plus enzyme buffer (RhoA MO); and 4) RhoA MO plus ChABC (RhoA MO+ChABC).Consistent with our previous findings, at 4-weeks post-transection, there was less caspase activation in the ChABC and RhoA MO groups than in the Ctrl group. Moreover, the RhoA MO plus ChABC group had the best protective effect on identified reticulospinal (RS) neurons among the four treatment combinations. At 2 weeks post-transection, when axons have retracted maximally in the rostral stump and are beginning to regenerate back toward the lesion, the axon tips in the three treatment groups each were closer to the transection than those in the Ctr MO plus enzyme buffer group. Long-term axon regeneration also was evaluated for the large, individually identified RS neurons at 10 weeks post-transection by retrograde. The percent regenerated axons in the RhoA MO plus ChABC group was greater than that in any of the other groups. Akt phosphorylation levels at threonine 308 was quantified in the identified RS neurons by western blots and immunofluorescence. The RhoA MO plus ChABC treatment enhanced Akt 308 phosphorylation more than any of the other treatment groups.Although some of the effects of CSPGs are mediated through RhoA activation, some growthinhibiting mechanisms of RhoA and CSPGs are independent of each other, so combinatorial therapies may be warranted.